Exploring Gen Z's Sharia-Compliant Purchasing Behaviour: Structural Impacts of Islamic Marketing, Halal Quality, and Online Shopping Lifestyle - Mahelan Prabantarikso; Maria Assumpta Wikantari; Karnawi Kamar; Aat Ruchiat Nugraha; Vita Briliana (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The growing halal industry and digital marketplace have reshaped Gen Z consumer behaviour, leading their purchase patterns to blend Islamic values with digital lifestyles. Although existing studies have examined Islamic marketing, product quality, and online consumer behaviour separately, limited research has modelled their combined effects on purchase decisions within a sharia-compliant framework. This study addresses this gap by developing a quantitative model that predicts Generation Z's purchase decisions, with customer satisfaction as the mediating variable. Using a survey-based design, data were collected from 53 Gen Z respondents and analysed using Structural Equation Modelling–Partial Least Squares (SEM–PLS). The study results show that consumer shopping habits significantly influence their level of satisfaction. Product quality has a significant impact on customer satisfaction. Sharia marketing has a substantial impact on customer satisfaction. Shopping lifestyle has a significant impact on purchasing choices. Product quality has a considerable impact on purchasing choices. Sharia marketing has a substantial effect on consumer purchasing decisions. Customer satisfaction significantly affects purchasing decisions. Globally, the study provides empirical evidence supporting the growing relevance of the halal economy and offers insights for policymakers and industries seeking to strengthen consumer trust and competitiveness.